(untitled) (Journal of Economic Research & Business Administration, 2016)
The article describes the basic concepts of sustainable development of the regions, the need for their better understanding for assessing the sustainability of the regions of Kazakhstan. The main indicators character izing the sustainable development of regions and the need to raise their calculation of the economy of the Republic of Kazakhstan.